Steady-State Creep Behaviour of Functionally Graded Silicone Rubber with Cellulose Addition - Jasem, Manal H.; A. Abbod, Esraa; A. Jassim , Tamara; Y. Hussien, Zainab; Omaraa, Ehsan (Journal of Engineering and Sustainable Development, 2025)
This study investigates the steady-state creep behaviour of functionally graded silicone rubber with cellulose addition. Functionally graded materials (FGMs) have a composition that gradually changes based on their volume, resulting in properties such as strength, thermal conductivity, and stiffness that vary from point to point. This work aims to examine the creep and thermal behaviour of silicone rubber with cellulose and determine the effect of cellulose content on the properties of this FGM. Different amounts (by weight) of cellulose (0%, 3%, 6%, 9%, and 12%) were added to a silicone rubber matrix, and creep tests were conducted on FGM samples. The results showed that as the amount of cellulose increased, creep resistance and heat conductivity improved. It follows that FGMs with a higher cellulose content are better able to withstand high temperatures and deformation when subjected to load, as opposed to those with a lower cellulose concentration. The viscoelastic behavior of the FGM samples was characterized using the Kelvin-Voigt model. This study shows that adding cellulose to silicone rubber increases its creep resistance but decreases its ultimate strength, making it more brittle and prone to cracking under abrupt loads. FGMs whose composition changes gradually